When beauty tamed the beast ebook - James, Eloisa (Fairy Tales, 2011)
"Eloisa James's writing is absolutely exquisite." —New York Times bestselling author Teresa Medeiros "Nothing gets me to a bookstore faster than a new novel by Eloisa James." —New York Times bestselling author Julia Quinn A wonderful spin on a much-beloved fairy tale, Eloisa James's When Beauty Tamed the Beast is heart-soaring and fun historical romance at its finest. No wonder People magazine raves about her books, saying, "Romance writing does not get much better than this." Eloisa's delightful take on Beauty and the Beast unfolds in Regency England, where a beastly, bad-tempered Earl matches wits with a brazen beauty who has vowed to make the handsome grump fall in love with her in two short weeks.